Efficiency in Magnocellular Processing: A Common Deficit in Neurodevelopmental Disorders - Brown, Alyse Christine; Peters, Jessica Lee; Parsons, Carl; Crewther, David Philip; Crewther, Sheila Gillard (Frontiers in Human Neuroscience, 2020)
Several neurodevelopmental disorders (NDD) including Developmental Dyslexia (DD), Autism Spectrum Disorder (ASD), but not Attention Deficit Hyperactive Disorder (ADHD) to date, are reported to show deficits in global motion processing. Such behavioural deficits have been linked to a temporal processing deficiency in the generalised M pathway as the dorsal stream vulnerability hypothesis (Braddick et al., 2003). However, to date there have been few studies assessing the temporal processing efficiency of the M pathways. On the basis that the magnocellular pathway supports higher temporal modulation compared with the Parvocellular pathway, we measured flicker fusion thresholds and autistic tendencies (using the Autism-spectrum Quotient) in a nonselective sample of NDDs and neurotypicals (mean age 10, range 7-12 years, n=71). The children were matched for both chronological age and nonverbal intelligence. The NDD participants presented with singular or comorbid combinations of Developmental Dyslexia (DD), Autism Spectrum Disorder (ASD), and Attention Deficit Hyperactive Disorder (ADHD). Results showed that ASD and DD including those with comorbid ADHD demonstrated comparable FFTs that were significantly lower than their matched control. Participants with a singular diagnosis of ADHD did not differ from the FFTs observed in their matched controls. Over the whole population, higher AQ score was found to correlate with lower FFT (r= -.269, p<.02 n=71). In conclusion, this study presents evidence showing that a temporally inefficient M pathway could be the unifying network at fault across the NDDs included in the dorsal stream vulnerability hypothesis. On this basis, singular ADHD appears to have a different causation - there was strong evidence for a less efficient M pathway in the ASD and DD diagnoses.